Polymerase delta-interacting protein 2 mediates brain vascular permeability by regulating ROS-mediated ZO-1 phosphorylation and localization at the interendothelial border - Keke Wang; Hongyan Qu; Ruinan Hu; Bernard Lassègue; Douglas C. Eaton; Chang Song; Jianjun Mu; Kathy K. Griendling; Marina S. Hernandes (Cell Communication and Signaling)
Abstract Background Polymerase delta-interacting protein 2 (Poldip2) is a novel regulator of vascular permeability that has been shown to be involved in aggravating blood–brain barrier (BBB) disruption following stroke; however, the underlying mechanisms are unknown. While endothelial tight junctions (TJ) are critical mediators of BBB permeability, the effect of Poldip2 on TJ function has not been elucidated yet. Here, we aim to define the mechanism by which Poldip2 mediates BBB disruption, specifically focusing on phosphorylation and stabilization of the TJ integral protein ZO-1. Methods and Results Cerebral ischemia was induced in endothelial-specific Poldip2 knockout mice and controls. Cerebral vascular permeability was assessed by Evans blue dye extravasation. Endothelial-specific Poldip2 deletion abolished Evans blue dye extravasation after ischemia induction. In vitro permeability assays demonstrated that Poldip2 knockdown suppressed TNF-α-induced endothelial cell (EC) permeability. Immunofluorescence staining showed that Poldip2 depletion prevented TNF-α-induced ZO-1 disruption at interendothelial junctions. Conversely, Poldip2 overexpression increased endothelial permeability, loss of ZO-1 localization at cell–cell junctions and enhanced reactive oxygen species (ROS) production. Treatment with the antioxidant N-acetyl cysteine (NAC) reduced Poldip2-induced ZO-1 disruption at inter interendothelial junctions. Immunoprecipitation studies demonstrated Poldip2 overexpression induced tyrosine phosphorylation of ZO-1, which was prevented by treatment with NAC or MitoTEMPO, a mitochondrial ROS scavenger. Conclusions These data reveal a novel mitochondrial ROS-driven mechanism by which Poldip2 induces ZO-1 tyrosine phosphorylation and promotes EC permeability following cerebral ischemia. Graphical Abstract